Study of runaway electrons in TUMAN-3M tokamak plasmas. (24th May 2018) - Shevelev, A; Khilkevitch, E; Tukachinsky, A; Pandya, S; Askinazi, L; Belokurov, A; Chugunov, I; Doinikov, D; Gin, D; Iliasova, M; Kiptily, V; Kornev, V; et al.
Abstract: Studies of runaway electrons in present day tokamaks are essential to improve theoretical models and to support possible avoidance or suppression mechanisms in future large-scale plasma devices. Some of the phenomena associated with the runaway electrons take place at faster time scales, and thus it is essential to probe the runaway electrons to investigate underlying physics. The present article reports a few experimental observations of runaway electron associated events, at fast time scales, using a state-of-the-art multi-detector system developed at the Ioffe Institute and recently deployed on the TUMAN-3M tokamak. The system is based on the high-performance scintillation gamma-ray spectrometers for measurements of bremsstrahlung generated during the interaction of accelerated electrons with plasma and materials of the tokamak chamber. It includes a total three detectors configured in the spectroscopic mode having different lines of sight. Along with this hardware, dedicated algorithms were developed and validated that enables the separation of piled-up pulses, maximize the dynamic range of the detector and provides a counting rate as high as 10 7 counts per second. The inversion code, DeGaSum, has been used for the reconstruction of a runaway electron energy distribution function from the measured gamma-ray spectra. Using this tool, experimental analysis of the runaway electron beam generation and evolution of their energy distribution in the TUMAN-3M representative plasma discharges is performed. The effect on gamma-ray count rate during the magnetohydrodynamic activities and possible changes in the runaway electron energy distribution function during sawtooth oscillations is discussed in detail. Possible maximum limit of the runaway electron energy in TUMAN-3M is investigated and compared with the numerical analysis. In addition, the probability of the runaway electron generation throughout the plasma discharge is estimated analytically and compared with the experimental observation that suggests a balance between production and loss of the runaway electrons.